PENGEMBANGAN BAHAN AJAR FISIKA YANG TERINTEGRASI NILAI-NILAI AYAT AL-QURAN PADA MATERI GERAK UNTUK PEMBELAJARAN SISWA KELAS X SMA - Sri Mardayani (PILLAR OF PHYSICS EDUCATION, 2013)
Teacher should facilitate the students in the learning process, one by providing teaching materials that match with students characteristics. Physics teaching materials which available is still not integrated by the values of Qur’an’s verses ​​ while in the learning process teachers using an integrated syllabus with the values ​​ of Qur’an’s verses. The general objective of this research was to develop teaching materials that integrated by the values of Qur’an’s verses for physics material Grade X about motion that has a good validity, practical, and effective . The type of this research is Research and Development (R & D). Teaching materials developed by using a four-D models consisting of four steps: define, design, develop, and disseminate. The exception for step disseminate is not performed. Based on the data analysis which has been done, it can present the research results. First, the teaching materials has a high validity with an average of 82.3 experts. Second, the value of practicality of teaching materials based on teacher assessment is 91.5 and the value of practicality of teaching materials based on students assessment is 93.7. Third, the value of effectively of teaching materials is 90.4. It’s signed by the increasing of physics student’s learning outcomes. Keywords: teaching materials, the relation between physics and Qur’an’s, the values from Qur’an’s verses, motion, physics learning